Electronic Complaint Management Based on Report Application on Infrastructure Management in Cirebon City - Tania Sahaya Putri Nurmayana; Elisa Susanti (Jurnal Manajemen (Edisi Elektronik), 2025)
The SP4N LAPOR application is designed to manage public complaints and enhance service quality. However, its implementation in Cirebon City faces challenges, including low responsiveness, lack of transparency, and limited public awareness. This study evaluates the effectiveness of the LAPOR application in handling infrastructure-related complaints by examining commitment, accessibility, responsiveness, transparency, accountability, privacy, and confidentiality. This research employs a descriptive qualitative approach, utilizing interviews, observations, and document analysis. Data were collected from purposively selected informants from the Communication and Informatics Agency (DKIS) and the Public Works and Spatial Planning Agency (DPUTR). Findings indicate that despite governmental support, challenges persist in training, technical assistance, and complaint resolution consistency. While accessibility is adequate, public engagement remains low. Responsiveness is hindered by delays and limited transparency. Accountability requires clearer information on complaint handling and responsible authorities. To optimize the LAPOR application’s effectiveness, this study recommends improving complaint management mechanisms, strengthening technological infrastructure, and enhancing public outreach.